Depression and coronary heart disease. Clinical characteristics, pathogenetic links and treatment issues - Monteleone, P.; Monteleone, A. M.; Steardo, L., Jr.; Maj, M. (Die Psychiatrie, 2012)
It is widely accepted that depression increases the risk of coronary heart disease (CHD) in healthy people while, in individuals with an existing heart disease, depression is a predictor of recurrent cardiac events and death. It seems that new-onset depression after an acute coronary syndrome (ACS) and not recurrent depression may worsen the cardiovascular outcome, and it has been suggested, although not conclusively proved, that depressive somatic symptoms, could be more cardiotoxic than depressive cognitive symptoms. Both psychosocial (low social support, less adherence to treatment recommendations, physical inactivity) and biological mechanisms (autonomic nervous system dysregulation, platelet and endothelial dysfunctions, inflammation, and neuroendocrine abnormalities) have been hypothesized to explain the link between depression and the increased risk of CHD or adverse cardiovascular prognosis. Randomized controlled clinical trials seem to suggest that depression in CHD patients is poor responsive to both pharmacological and psychotherapeutic treatments. Nevertheless, these trials provide also a robust evidence that CHD depressed patients non responder to antidepressant treatments are at greater risk of adverse cardiac event than patients with successfully treated depression. Therefore, it is advisable that psychiatrists, cardiologists and general practitioners coordinate their efforts in managing depression in CHD patients.
Keywords: Depression; coronary heart disease; myocardial infarction